Inactivation of microorganisms by high isostatic pressure processing in complex matrices: A review. (February 2015) - Georget, E.; Sevenich, R.; Reineke, K.; Mathys, A.; Heinz, V.; Callanan, M.; Rauh, C.; Knorr, D.
Abstract: The benefits of high pressure processing (HPP) for microbial inactivation in food production include reduced thermal treatment and minimized effects on sensory and nutritional profiles. These benefits have resulted in increasing commercial production of high pressure pasteurized foods. In this review, the current state of the art in terms of vegetative cell and bacterial spore inactivation by HPP in complex food matrices is assessed with an emphasis on mechanisms of inactivation and treatment of products that have low or non-uniform water activity (aw ) profiles. Low aw can be the result of a high concentration in solutes, the presence of oils/fats, or the physical removal of water through dehydration. Microbial inactivation in low aw environments remains a particular challenge for HPP and studies on microbial inactivation observed in the different types of low aw food matrices are reviewed in detail. Industrial relevance: HPP-treated food products with low aw have been on the market since the nineties, but the mechanisms of microbial inactivation at low aw are still not well understood, which hinders the development of new applications in low or inhomogeneous aw food. This review summarizes the state of the art in terms of HPP microbial inactivation mechanisms in model systems and various low aw food environments. Thereby, it identifies existing and potential new applications as well as the current gaps and future research needs. Highlights: HPP benefits have led to increasing commercial production of HP preserved foods. Microorganism inactivation by HPP in complex food matrices is reviewed. Emphasis is set on inactivation mechanisms in low or non-uniform aw products. aw alone is not sufficient to explain disparities in inactivation. Matrix specificities must be considered in addition to aw protection effect.